2009
DOI: 10.1590/s1984-46702009000400021
|View full text |Cite
|
Sign up to set email alerts
|

Ecological parameters of the endohelminths in relation to size and sex of Prochilodus argenteus (Actinopterygii: Prochilodontidae) from the Upper São Francisco River, Minas Gerais, Brazil

Abstract: This research aimed to investigate the ecological indexes of the helminths of the digestive system and coelom of Prochilodus argenteus Spix & Agassiz, 1829. A total of 150 specimens (53 males and 97 females) taken from the upper reaches of the São Francisco River in the municipality of Três Marias (18º12'32"S, 45º15'41"W), State of Minas Gerais, Brazil, were examined. The specimens were collected in July, 2003 and January, 2004. Ninety-eight fish (65.3%) were infected by at least one species of helminth. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Subsequently, these fish acquire new parasite species in their new habitat MORAND, 2004). Since C. kelberi is an exotic species, it is possible that the proteocephalid cestodes that were found had been introduced in conjunction with their hosts, because no other species of fish from the Três Marias Reservoir in the upper São Francisco River region, whose parasitic fauna was investigated, presented with such helminths SANTOS, 2003SANTOS, , 2005SANTOS;BRASIL-SATO, 2006;SANTOS, 2008;MONTEIRO et al, 2009). Lacerda et al (2013b) accepted this hypothesis when they verified that both species of proteocephalids present in C. piquiti Kullander & Ferreira, 2006, from the original environment (Lajeado Reservoir and São Salvador, Tocantins River) continued to parasitize those hosts that were introduced in new places (Jupiá and Itaipu Reservoirs, Paraná River).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, these fish acquire new parasite species in their new habitat MORAND, 2004). Since C. kelberi is an exotic species, it is possible that the proteocephalid cestodes that were found had been introduced in conjunction with their hosts, because no other species of fish from the Três Marias Reservoir in the upper São Francisco River region, whose parasitic fauna was investigated, presented with such helminths SANTOS, 2003SANTOS, , 2005SANTOS;BRASIL-SATO, 2006;SANTOS, 2008;MONTEIRO et al, 2009). Lacerda et al (2013b) accepted this hypothesis when they verified that both species of proteocephalids present in C. piquiti Kullander & Ferreira, 2006, from the original environment (Lajeado Reservoir and São Salvador, Tocantins River) continued to parasitize those hosts that were introduced in new places (Jupiá and Itaipu Reservoirs, Paraná River).…”
Section: Discussionmentioning
confidence: 99%
“…In the Upper Paraná River plain (Brazil), Lizama et al (2005) recorded nematode Raphidascaris sp, in a very low prevalence (approximately 2%). In the case of S. asperus, in various studies carried out in Neotropical environments, it was found in different parts of the digestive tract of Prochilodontidae, including P. lineatus, P. scrofa, P. argenteus and P. reticulatus (Travassos et al 1928, Fernandes et al 1982, Petter & Morand 1988, Ramallo 1999, Santos et al 2003, Monteiro et al 2009, Reis et al 2017, Leite et al 2018, Lehun et al 2020, Ramallo et al 2020. In Argentina, the records of S. asperus parasitizing P. lineatus correspond to the Paraná River in the area of its confluence with the Paraguay River, Corrientes (Hamann 1982a), the Río Hondo reservoir, Santiago del Estero (Ramallo 1999) and the Pilcomayo River, Salta (Ramallo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mature specimens of proteocephalids have been recorded in the following top-of-chain predatory fish species in the upper São Francisco river: Characiformes -Salminus brasiliensis (Cuvier, 1816) (= Salminus franciscanus Lima & Britski, 2007) (Brasil-Sato, 2003; Siluriformes -Pseudoplatystoma corruscans (Spix & Agassiz, 1829) (Brasil-Sato, 2003); and Perciformes -Cichla kelberi Kullander & Ferreira, 2006(Santos-Clapp & Brasil-Sato, 2014. Plerocercoids have been reported in many fish species in the upper São Francisco river: Characiformes -Prochilodus argenteus Spix & Agassiz, 1829 (Monteiro et al, 2009), P. piraya (Santos-Clapp et al, 2022, in press), Salminus hilarii Valenciennes, 1850 (Duarte et al, 2016) and Tetragonopterus chalceus Spix & Agassiz, 1829 and Triportheus guentheri (Garman, 1890) (Albuquerque et al, 2016); and Siluriformes -Pimelodus maculatus Lacepède, 1803(Brasil-Sato, 2003 and Pimelodus pohli Ribeiro & Lucena, 2006(Sabas & Brasil-Sato, 2014. In A. lacustris, which is an expert predator, only the larvae of these proteocephalids formed part of their parasite community, but with elevated indexes, and these were dominant in the communities of six out of these eight lagoons sampled in the upper and middle São Francisco river.…”
Section: Discussionmentioning
confidence: 99%